High Frequency of RPL22 Mutations in Microsatellite‐Unstable Colorectal and Endometrial Tumors. Issue 12 (December 2014) - Ferreira, Ana M.; Tuominen, Iina; van Dijk‐Bos, Krista; Sanjabi, Bahram; van der Sluis, Tineke; van der Zee, Ate G.; Hollema, Harry; Zazula, Monika; Sijmons, Rolf H.; Aaltonen, Lauri A.; Westers, Helga; Hofstra, Robert M.W.
<x xml:space="preserve">Abstract</x> RPL22 mutations suggest genes coding for ribosomal proteins as new candidates for target genes in microsatellite unstable tumours. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>